A comparative analysis of the live and recorded versions of crazy in love by Beyonce / Mohd. Zairul Azreen Shah Mohd. Bakhari - Mohd. Bakhari, Mohd. Zairul Azreen Shah (2014)
Singer and actress Beyonce Giselle Knowles was born on September 4, 1981, in Houston, Texas. She started singing at an early age, competing in local talent shows and winning many of these events by impressing audiences with her natural singing and dancing abilities. Beyonce Knowles is a multi-platinum, Grammy Award-winning recording artist who's acclaimed for her thrilling vocals, videos and live shows. (Caramanica J. 2014) Crazy in love is a successful debut solo by Beyonce. This debut single featuring rapper and her now-husband, Jay-Z are in her debut solo album, Dangerously In Love. Crazy In Love is an R&B and pop love song which incorporates elements of 1970s-style funk and hip hop, as well as soul. (Dorian L. 2006) The lyrics reference a romantic obsession that causes her to act out of character. Producer Rich Harrison, Beyonce and Jay-Z wrote and composed the song and Columbia Records release this single on 20 May, 2003. (Lisa Verrico 2003) This single was Beyonce's first number one single as a solo artist in the United States, peaking on the Billboard Hot 100 chart for eight consecutive weeks. This single also ranked 118th on Rolling Stone's 2010 list of the 500 greatest songs of all time. At the 46th Grammy Awards, it won Grammys for Best R&B Song and Best Rap/Song Collaboration.